2015
DOI: 10.1177/1934578x1501001016
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Cultivars and Phenological Phases on the Accumulation of Nevadensin and Salvigenin in Basil{Ocimum basilicum)

Abstract: According to the earlier literature the optimum harvest time for basil is at the full flowering stage if accumulation of essential oil is taken into account. In this research we have investigated our gene-bank stored basil accessions to determine whether the harvest timing is variety specific or not considering their flavonoid accumulation pattern. In our work we have determined by HPLC the content of two main flavonoid compounds, salvigenin and nevadensin, of eight different gene bank accessions from 2013 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Polar solvents such as methanol, ethanol, and aqueous mixtures have been used to obtain extracts from species including O. basilicum, O. gratissimum, O. sanctum, and O. tenuiflorum with good results [84,[99][100][101][102][103][104]. Less used, but also effective in the extraction of flavones, are solvents such as diethyl ether, which is useful to extract such flavones as nevadensin and salvigenin in O. basilicum [105]. Fewer studies were observed with other solvents such as hot water extract that showed similar results to hydromethanolic and hydroethanolic extractions in the same plant [106].…”
Section: Extraction Methods Of Flavones From Lamiaceae Plants 41 Conventional Methodsmentioning
confidence: 99%
“…Polar solvents such as methanol, ethanol, and aqueous mixtures have been used to obtain extracts from species including O. basilicum, O. gratissimum, O. sanctum, and O. tenuiflorum with good results [84,[99][100][101][102][103][104]. Less used, but also effective in the extraction of flavones, are solvents such as diethyl ether, which is useful to extract such flavones as nevadensin and salvigenin in O. basilicum [105]. Fewer studies were observed with other solvents such as hot water extract that showed similar results to hydromethanolic and hydroethanolic extractions in the same plant [106].…”
Section: Extraction Methods Of Flavones From Lamiaceae Plants 41 Conventional Methodsmentioning
confidence: 99%